Factors Supporting Independence of Children during Transition to School. Theoretical Overview - Anastasiya K. Nisskaya; Arina S. Chuvilina (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
Among the challenges faced by first-graders at the beginning of schooling, a special place is occupied by the development of independence, including in learning activities. It requires cognitive initiative, the ability to independently plan, predict and implement learning activities, to control and evaluate them. At the same time, the skills of independence (everyday, communicative, cognitive) developed in preschool age can be leveled in the case of a difficult transition to school.The question arises as to what ways to support children's independence during the transition from kindergarten to school are described by modern researchers and practitioners. Analysis of the literature has allowed us to formulate an idea of the complex nature of this support. Among its factors, attention and consideration of the age-psychological and individual characteristics of the child can be highlighted; the supportive and consistent position of the family and the involvement of parents in education; the rejection of universal strict requirements in favor of flexibility, sensitivity to the needs of the child and encouraging his independence in preschool education; adequate teacher expectations for the child, the possibility of individualization of education and purposeful development SENG is in the first grade; consistency ("continuity", "continuity") of goals, approaches and methods of organizing the educational process in the family, preschool organization and school.